A study on the teaching reform of the course of teacher writing skills for teacher trainees in colleges and universities - Li, Zhen (Pacific International Journal, 2024)
To promote the art of calligraphy and inherit the excellent traditional Chinese culture, it is necessary to strengthen calligraphy education in primary and secondary schools, expand the influence of Chinese character writing education, and comprehensively improve students’ writing literacy. However, studies have found that primary and secondary school students’ ability to write Chinese characters has weakened, which is naturally related to the weakening of pen-and-paper writing in the information age, but also to the insufficient understanding of calligraphy education in school education and the lack of effective guidance from teachers for students. Teachers’ writing level has a profound impact on students, and the demand for teachers to teach calligraphy in basic education poses a challenge to the writing skills of teacher trainees in colleges and universities. However, the current writing skills courses for teachers in colleges and universities have problems such as unclear positioning of the curriculum, the overall quality level of teachers needs to be improved, the skills training of the courses is not prominent enough, and the assessment system is not sound. Accordingly, the path of teaching reform of teachers’ writing skills course is proposed: first, adjusting teaching objectives; second, reconstructing teaching modules; third, improving assessment methods; and fourth, carrying out diversified teaching activities.